Identification of Three New Genes Involved in Morphogenesis and Antibiotic Production in Streptomyces coelicolor - Sprusansky, Ondrej (American Society for Microbiology, 2003)
We report the isolation and partial characterization of three new mutants of Streptomyces coelicolor that are defective in morphogenesis and antibiotic production. The genes identified by the mutations were located and cloned by using a combination of Tn5 in vitro mutagenesis, cotransformation, and genetic complementation. Mutant SE69 produces lower amounts of antibiotics than the wild type produces, produces spores only after prolonged incubation on rich media, and identifies a gene whose predicted protein product is similar to the GntR family of transcriptional regulators; also, production of aerial mycelia on both rich and poor media is significantly delayed in this mutant. Mutant SE293 is defective in morphogenesis, overproduces antibiotics on rich media, fails to grow on minimal media, and identifies a gene whose predicted protein product is similar to the TetR family of transcriptional regulators. Preliminary evidence suggests that the SE293 gene product may control a molybdopterin binding protein located immediately adjacent to it. Mutant SJ175 sporulates sooner and more abundantly than the wild type and overproduces antibiotics on rich media, and it identifies a gene whose predicted protein product contains regions of predominantly hydrophobic residues similar to those of integral membrane proteins.